Assessing Malaysian disaster preparedness for flood - Harith, Noorhashirin; Mohd Tohit, Nor Faiza; Rusli, Mohammad Farhan; Juni, Muhamad Hanafiah (Department of Community Health, Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2016)
Flood has been one of the most recurring disasters in Malaysia since the early 1920’s. Previously it was limited to the city centre with flash floods occurring at various intervals. With the major development and expansion of the country as a whole, various states especially those located in the eastern coastal regions have been badly affected over the recent years. The capital Kuala Lumpur has also not been spared. Various agencies play a role in the mitigation and preparedness in the event of a flood disaster and this article aims to look at the strategic planning and also assess the Malaysian disaster preparedness as a whole. They are however very limited papers and research done on the disaster preparedness in Malaysia, and the majority of the paper has used guidelines, Acts and Laws, reports and also direct Ministerial regulations to help assess the disaster preparedness plan in Malaysia. The paper found that there are many areas of assessment and key agencies involved. The disaster plan in Malaysia at present is not perfect and there is much room for improvement and upgrading.